Abce1 orchestrates M-phase entry and cytoskeleton architecture in mouse oocyte - Jiao, Xiao-Fei (Oncotarget, 2017)
ATP-binding cassette E1 (ABCE1) is a member of the ATP-binding cassette transporters and essential for diverse biological events regulating abroad range of biological functions including viral infection, cell proliferation, anti-apoptosis, translation initiation and ribosome biogenesis. Here, we discovered that Abce1 also plays indispensable roles in mouse oocyte meiotic progression. In the present study, we examined the expression, localization, and function of Abce1 during mouse oocyte meiotic maturation. Immunostaining and confocal microscopy identified that Abce1 localized as small dots in nucleus in germinal vesicle stage. After germinal vesicle breakdown, it dispersedly localized around the whole spindle apparatus. During the anaphase and telophase stages, Abce1 was just like a cap to localize around the two pole region of spindle but not the midbody and chromosome. Knockdown of Abce1 by specific siRNA injection delayed the resumption of meiosis (GVBD) and affected the extrusion of first polar body. Moreover, the process of spindle assembly and chromosome alignment were severely impaired. Abce1-RNAi led to the dissociation of γ-tubulin and p-MAPK from spindle poles, thus caused mounts of spindle morphology abnormities and chromosome alignment defects, leading to high incidence of aneuploidy. Our findings refresh the knowledge of Abce1 function by exploring its role in oocyte meiotic resumption, spindle assembly and chromosome alignment.